Upaya-upaya yang Dilakukan Polisi Air Polda Bali dalam Mencegah Masuknya Imigran Gelap - Andi Alfian Hedar; Sobandi; Komang Edy Darma Saputra (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Indonesia, as an archipelagic country, holds a geographically strategic position while also being vulnerable to various forms of transnational crimes, including the entry of illegal immigrants via maritime routes. Law enforcement in maritime areas presents its own challenges due to the need to monitor vast territories, limited facilities and infrastructure, as well as the complex modus operandi employed by illegal immigration offenders. In this context, the Water Police (Pol-Air) serves as the main actor in maintaining maritime security and order, particularly in efforts to prevent the entry of illegal immigrants. This study aims to analyze the strategies and actions undertaken by Pol-Air in performing this function, as well as to evaluate the obstacles faced. The research method used is normative legal research with a qualitative approach, through analysis of existing laws and regulations as well as empirical practices in the field. The results of the study indicate that Pol-Air conducts various preventive measures, such as routine sea patrols in vulnerable areas, the use of maritime surveillance technology, improvement of personnel competencies, and public dissemination of immigration law among coastal communities as a form of participatory prevention. In addition, Pol-Air also engages in cross-sectoral coordination with relevant agencies to strengthen institutional synergy. Nevertheless, the implementation of Pol-Air's duties still faces structural and operational challenges, such as budget limitations, lack of integrated information systems, and weak law enforcement against human smuggling networks. Therefore, a reformulation of policies is needed to support institutional strengthening and sustainable inter-agency collaboration.